Sistem Pendukung Keputusan Rekomendasi Karyawan Tetap Menggunakan Metode Weighted Product - Dwi Yulian Rachmanto Lingke; Handri Kurnianto (Jurnal SIFO Mikroskil, 2017)
At the PT. Kertas Basuki Rachmat Banyuwangi there are some employees who have the status of contract employees and permanent employees. But the status of contract employees can be promoted to full-time employees. One was through the recommendation of the superintendent reported to the HRD (Human Resources Development). Recommendations of the head part to promote employee contracts into permanent employees through several selection criteria of certain specified companies, these criteria are: Discipline, Work Experience, Insight, Teamwork, Behavior, Loyalty and Responsibility. Then the need to design a decision support system using the method of calculation process Weighted Product Model (WPM) based on criteria specified company. This research resulted in applications that provide the same recommendation with the results of manual counting with a good accuracy, so that applications created to help support the decision of recommendation from the head portion to the HRD to determine who the candidates eligible to be promoted as permanent employees are more competent in the field which he held